Oxidative stress: The nexus of obesity and cognitive dysfunction in diabetes - Li, Huimin; Ren, Jing; Li, Yusi; Wu, Qian; Wei, Junping (Frontiers in Endocrinology, 2023)
Abstract: Obesity is strongly associated with oxidative stress. Obese patients are at increased risk of diabetic cognitive dysfunction, suggesting a pathological link between obesity, oxidative stress, and diabetic cognitive dysfunction. Obesity can induce the biological process of oxidative stress by disrupting the adipose microenvironment (adipocytes, macrophages), mediating chronic low-grade inflammation, and mitochondrial dysfunction (mitochondrial division, fusion). At the same time, oxidative stress can be involved in insulin resistance, induction of inflammation in neural tissues, and lipid metabolism disorder processes, which in turn affect the development of cognitive dysfunction in diabetes.